TINJAUAN YURIDIS TERHADAP PUTUSAN KASUS TINDAK PIDANA PENGANIAYAAN (STUDI KASUS PUTUSAN PIDANA NOMOR: 96/PID.B/PN.CJR): Juridical Review of The Verdict In The Case Of Persecution (Case Study Of Criminal Decision Number: 96/Pid.B/Pn.Cjr) - Rofaeda Arisia Salsabila Tanjung; Ermania Widjajanti (Universitas Trisakti, 2024)
The crime of maltreatment often occurs due to a misunderstanding or a sense of resentment/offense against another person so that the perpetrator takes it out by committing maltreatment, as is the case in Criminal Decision Number: 96/Pid.B/2020/PN Cjr who committed maltreatment due to a sense of resentment/offense against the victim causing injury. The issues raised are 1) Whether the defendant's actions fulfill the formulation of Article 351 paragraph 1 of the Criminal Code (Study of Decision Number 96/Pid.B/2020/PN Cjr) and 2) Is the punishment imposed on the defendant in accordance with the purpose of punishment? This research was conducted using normative juridical research type with descriptive analytical nature with secondary data which was analyzed qualitatively and a deductive logic conclusion was drawn. The results showed that the actions committed by the defendant had fulfilled the formulation of Article 351 paragraph (1) of the Criminal Code but were not precise because the victim suffered serious injuries and the defendant's actions basically constituted serious maltreatment so that the Judge should have imposed Article 351 paragraph (2) of the Criminal Code in accordance with the objectives of the theory of punishment, namely to provide protection of the public welfare and balance and harmony of life by taking into account the interests of the state, society, victims, and perpetrators